The Effect of Bingo Game on the Students’ Pronunciation and Interest in Learning English - Dasmasela, Milka Levlin; Nursalim, Nursalim; Wardani, Rizqi Claudia (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The aim of this research is to find out whether bingo Game can help students with pronunciation and can attract students’ interest in taking English classes. Related to the research objectives using pre-experimental research. The research population was class VIII students of SMP Negeri 26 Kabupaten Sorong. In collecting data, researchers used 30 Vocabulary for pre-test and post-test. In analyzing the data, researchers used SPSS 20 to calculate the data. After analyzing the T-Sample test results, the alternative hypothesis states that the Bingo Game media has an impact on the pronunciation and interest of students at SMP Negeri 26 Sorong Regency, especially students in class VIII and the Null hypothesis is rejected. Apart from that, the result of P-Value (.000) is smaller than P.Value (0.01), which means that students comprehension scores between pre-test and post-test are significantly different and it can be concluded that the bingo game has an impact on students pronunciation and interest at SMP Negeri 26 Kabupaten Sorong